Impacts of COVID-19 on the Life of Eunuch's (Hijras) in Hyderabad, Sindh Province of Pakistan - Sanjrani, Darya Khan; Khoso, Abdul Rasool; Mallah, Sajjad Ali; Akhtar, Farhan; Bhutto, Shahnaz; Narejo, Nasir Ali; Vighio, Kainat (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to describe the impacts of covid-19 on the life of eunuchs (hijra) in district Hyderabad, Sindh, Pakistan. To investigate the effects of covid-19 on the life of a eunuch, in-depth interviews were performed on the eunuch by birth. They included Guru, usually the leader of that particular group. Three Chelas who are the followers of the sample were collected through the snowball sampling technique qualitatively and were analyzed manually. Based on the interviews, the results revealed that eunuchs were facing a lot of predicament during COVID-19 because eunuchs were dependent on begging, dancing, and involved on the different local meetings, which were totaled due to COVID-19. Conversely, in that situation, the eunuchs were being ignored by the people, and no funding was provided to support them. Though, internationally they need to be given all those rights as the locally met. The study findings are supportive and can potentially guide the intervention plans for enhancing the life of eunuch community people. Since the study concludes that 'Eunuchs' are not enjoying their actual rights as met. Finally, the study recommends that there must be active policies for eunuchs, which should highlight the same enjoyments for eunuchs as completed by the local people.